Structure of nanostructured layered double hydroxides according to x-ray diffraction analysis data. Issue 1 (May 2020) - Popkov, A; Gabdrakhimova, E; Sharafieva, Z; Isakov, D
Abstract: Nowadays, in many areas of industry, in particular, the petrochemical industry, the problem of multifunctional, efficient and environmentally friendly materials use is of great importance. One such material is double layered hydroxides (LDHs) used in various synthesis reactions, catalytic and adsorption processes. This paper presents studies on the effect of the elemental composition of LDH on their structure. Under experimental conditions, 4 samples of LDHs based on Mg and Al, Mg and Fe, Zn and Al (2 samples with different cation ratios) were synthesized by co-precipitation of a base solution with a mixture of M(II) and M(III) salts solution. The phase composition of the obtained LDHs were analyzed by powder x-ray diffraction method. During the experiment, the characteristics of the Zn-Al LDH samples turned out to be lower than MgFe and MgAl LDHs due to the presence of a phase of zinc oxides in their composition, as well as the structure of the obtained products. Similarly, the size of ZnAl crystallites of LDH at a trivalent cations share of 0.33 compared to 0.4 was larger by about 3.5 times.